Taco Cart Lesson, a Three Act Task (pp. 91--106) - Dietz, Hannah (Ohio Journal of School Mathematics, 2020)
The author offers a revision of a lesson plan which uses Dan Meyer’s Three Act Task format tolead students through a problem involving the Pythagorean Theorem. The Taco Cart problem uses a reallife situation to engage students. The research-based revisions that the author offers helps increase clarityfor students and teachers.